Quantifying the Spatial Variations of Hyporheic Water Exchange at Catchment Scale Using the Thermal Method: A Case Study in the Weihe River, China - Junlong Zhang; Jinxi Song; Yongqing Long; Yan Zhang; Bo Zhang; Yuqi Wang; Yuanyuan Wang (Advances in Meteorology)
Understanding the dynamics of hyporheic water exchange (HWE) has been limited by the hydrological heterogeneity at large catchment scale. The thermal method has been widely used to understand water exchange patterns in a hyporheic zone. This study was conducted in the Weihe River catchment in Shaanxi Province, China. A conceptual model was developed to determine water transfer patterns, and a one-dimensional heat diffusion-advection equation was employed to estimate vertical fluxes of ten different segments in the hyporheic zone in various ten segments of the catchment. The amount of water exchange varied from 78.47 mm/d to 23.66 mm/d and a decreasing trend from the upstream to downstream of catchment was observed. The spatial correlation of variability between the water exchange and distance is 0.62. The results indicate that mountain’s topography trend is the primary driver influencing the distribution of river tributaries, and the water exchange amount has a decreasing trend from upstream to downstream of the main river channel.